Habenular Stimulation for Neurosurgery Resistant Obsessive-Compulsive Disorder: A Case Report - Zhang, Chencheng; Zhang, Yingying; Li, Dianyou; Deng, Zhengdao; Nuttin, Bart; Voon, Valerie; Sun, Bomin (Frontiers in Psychiatry, 2020)
Background: Some patients suffer from persistent and severely disabling OCD symptoms that cannot be alleviated by conventional treatments or neuroablative interventions targeting cortico-striatal loop circuits. Currently, it is unclear how to manage the clinical symptoms of these unique patients. We reasoned that deep brain stimulation (DBS) of the habenula (HB) could be a valuable subsequent treatment option for these otherwise medically intractable cases of severe OCD. The HB is an epithalamic structure critically involved in the encoding and responding to aversive stimulus events, cognitive and brain processes known to be impaired in many patients with OCD. Similarly, HB DBS can alleviate depression and anxiety, which often co-occur with OCD. Here, we explore the clinical benefits and risks of HB DBS treatment in a patient with severe and refractory OCD. Case presentation: A 30-year-old male patient presented with persistent and severely disabling OCD symptoms that were refractory to previous psychological and pharmacological treatments, as well as to neuroablative surgical interventions involving both capsulotomy and cingulotomy. After HB DBS, however, the severity of the patient’s OCD symptoms was markedly reduced at 1-month follow-up, which was sustained until the final (at 12-month) follow-up. The patient also reported enduring improvements in depression, anxiety, and health-related quality of life after several months of HB DBS treatment. Conclusions: This case report provides the first clinical evidence suggesting that HB DBS could serve as a safe and effective alternative neurosurgical intervention for severe and refractory OCD. The present findings are promising and warrant further research into the role of the HB in pathophysiology and treatment of OCD.